2018
DOI: 10.1007/s13201-018-0664-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of detergents from laundry greywater on soil properties: a preliminary study

Abstract: Detergent compounds are classes of the organic micro-pollutants in the laundry wastewater. The disposal of these compounds into the soil has several adverse effects on their composition. In the present study, changes in the soil characteristics, which included saturated hydraulic conductivity (K sat ), EC, pH, exchangeable sodium percentage, cation exchange capacity (CEC), and sodium adsorption on ratio were examined after the irrigation with laundry wastewater. Ten clothes were washed with one full cap of pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 15 publications
4
15
0
Order By: Relevance
“…This finding is consistent with many studies that soil pH tend to increase with the reduction in soil salinity (Wang et al 2012;Li et al 2015). The increase in soil pH may be due to that the part of adsorbed Na in soil colloids dissociates with the soil desalinization, and consequently produces OH − , which enhances the pH of the soil solution (Mohamed et al 2018). This indicated that alkalization occurred in the soils of the raised bed as salt was leached by rainfall.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with many studies that soil pH tend to increase with the reduction in soil salinity (Wang et al 2012;Li et al 2015). The increase in soil pH may be due to that the part of adsorbed Na in soil colloids dissociates with the soil desalinization, and consequently produces OH − , which enhances the pH of the soil solution (Mohamed et al 2018). This indicated that alkalization occurred in the soils of the raised bed as salt was leached by rainfall.…”
Section: Discussionsupporting
confidence: 91%
“…The CEC value at each varying depth for GCS at Ibadan increased relative to CEC value of CS. This is in agreement with similar increase in CEC for surfactant-rich soil obtained by Mohamed et al (2018a) and Siggins et al (2016). For Isolu samples, the CEC value of Isolu GCS increased over that of CS only at 0.5 m depth.…”
Section: Physico-chemical and Hydraulic Propertiessupporting
confidence: 90%
“…The pH of GCS at Ibadan increased for each sampling depth when compared with control pH value but only increased at 0.5 m depth for GCS at Isolu. The increase in soil pH for GCS at Ibadan agrees with results of Mohamed et al (2018a), Siggins et al (2016) and Shifa and Thomas (2017) that reported increase in pH of soil contaminated with laundry detergent. The decrease in soil pH of Isolu GCS relative to control pH value at 1.0 and 1.5 m is in line with decreased soil pH in soil irrigated with greywater reported by Mohamed et al (2013).…”
Section: Physico-chemical and Hydraulic Propertiessupporting
confidence: 89%
See 1 more Smart Citation
“…However, after DOM and HLS were diluted to concentrations of 5 g L −1 , they had lower electrical conductivity (20 mS cm −1 , on average) than SHS, which meant that SHS had a greater effect on soil salinity than DOM or HLS. Too high concentration of sodium in soil might increase the possibility of its toxicity to plants and it might cause soil aggregates to crumple and spread which leads to poor water retention (Mohamed et al 2018).…”
Section: Washing Agent Characteristicsmentioning
confidence: 99%